The C5a/C5aR1 Axis Contributes to the Pathogenesis of Acute Cystitis Through Enhancement of Adhesion and Colonization of Uropathogenic E. coli - Wu, Kun-Yi; Cao, Bo; Wang, Chun-Xuan; Yang, Xue-Ling; Zhao, Shu-Juan; Diao, Teng-Yue; Lin, Li-Rong; Zhao, Guo-Xiu; Zhou, Wuding; Yang, Ju-Rong; Li, Ke (Frontiers in Cellular and Infection Microbiology, 2022)
Our previous work using a murine model of pyelonephritis demonstrated that the C5a/C5aR1 axis plays a pathogenic role in acute kidney infection. In this study, we report that the C5a/C5aR1 axis also plays a pathogenic role in acute bladder infection. C5aR1-deficient mice had reduced bladder bacterial load and attenuated bladder tissue injury, which is associated with reduced expression of terminal α-mannosyl residues (Man) (a potential ligand for type 1 fimbriae of E. coli) at the luminal surface of the bladder epithelium and reduced early bacterial colonization of the bladder. In vitro, C5a stimulation enhanced mannose expression in and facilitated bacterial adhesion/colonization to human bladder epithelial cells. C5a stimulation also upregulated the activation of ERK1/2 and NF-κB signaling and gene expression of proinflammatory cytokines (i.e., Il6, Il1b, Cxcl1, Ccl2) in the epithelial cells, which could drive pro-inflammatory responses leading to tissue injury. Administration of the C5aR1 antagonist effectively reduced bladder bacterial load and tissue injury. Thus, our findings demonstrate a previously unknown pathogenic role for the C5a/C5aR1 axis in bladder infection and suggest that the C5a/C5aR1 axis-mediated upregulation of Man expression, enhancement of bacterial adhesion/colonization, and excessive inflammatory responses contribute to acute bladder infection. These findings improve our understanding of the pathogenesis of bladder infection with therapeutic implications for UTI.